UPAYA MENINGKATKAN KETERAMPILAN MENGIDENTIFIKASI UNSUR INTRINSIK TEKS FIKSI MENGGUNAKAN METODE SAVI PADA SISWA SD - Evadeti, Evadeti (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2019)
AbstractThis research was motivated by students who had the difficulties in identifying intrinsic elements of fictional texts especially character, theme, setting, plot, and moral value. Research problem is how to improve the skill to identify the intrinsic elements of fictional text method using SAVI in SD 04 Sepahat. This research used descriptive method of the qualitative form. The procedures in this research was Classroom Action Research (PTK) and four stages of planning, action, observation, and reflecting. Data source was from students and teachers. The data was obtained from the RPP, the learning process and the test results.The data collection techniques was observation, measurement, and documentary study. The data collection tool used in this research was observation, tests, and documentation. The data analysis technic in this research was descriptive comparative and critical analysis technic. The instruments were the study results and the observation sheet. The results showed the SAVI method can improve the skills of identifying intrinsic elements of fictional text and students’ attitude in learning. The increase can be seen from the result of the action I which was 71.60, the result of the Act II which was 81.60, and result of action III which was 86.80. Keywords: identify, short story, SAVI